Peripheral endothelial function can be improved by daily consumption of water containing over 7 ppm of dissolved hydrogen: A randomized controlled trial - Ishibashi, Toru; Kawamoto, Kosuke; Matsuno, Kasumi; Ishihara, Genki; Baba, Takamichi; Komori, Nobuaki (PloS one, 2020)
Measurement of the reactive hyperemia index (RHI) using peripheral arterial tonometry (PAT) has shown benefits in the evaluation of vascular endothelial function and prediction of cardiovascular disease prognosis. Thus, it is important to examine the factors that promote the RHI. In this study, we aimed to investigate the effect of molecular hydrogen (H2) on reactive hyperemia-PAT of the small arteries of fingers in healthy people. To determine the efficacy of H2 for improving peripheral vascular endothelial function, water containing high H2 concentrations was administered to participants, and the Ln_RHI was measured in the finger vasculature. Sixty-eight volunteers were randomly divided into two groups: a placebo group (n = 34) that drank molecular nitrogen (N2)-containing water and a high H2 group (n = 34) that drank high H2 water (containing 7 ppm of H2: 3.5 mg H2 in 500-mL water). The Ln_RHI was measured before ingesting the placebo or high H2 water, 1 h and 24 h after the first ingestion, and 14 days after daily ingestion of high H2 water or the placebo. The mixed effects model for repeated measures was used in data analysis. The high H2 group had a significantly greater improvement in Ln_RHI than the placebo group. Ln_RHI improved by 22.2% (p<0.05) at 24 h after the first ingestion of high H2 water and by 25.4% (p<0.05) after the daily consumption of high H2 water for 2 weeks. Daily consumption of high H2 water improved the endothelial function of the arteries or arterioles assessed by the PAT test. The results suggest that the continuous consumption of high H2 water contributes to improved cardiovascular health.